2012
DOI: 10.1021/ja211888a
|View full text |Cite
|
Sign up to set email alerts
|

Photoswitchable Nanoparticles for Triggered Tissue Penetration and Drug Delivery

Abstract: We report a novel nanoparticulate drug delivery system that undergoes reversible volume change from 150 to 40 nm upon phototriggering with UV light. The volume change of these monodisperse nanoparticles comprising spiropyran, which undergoes reversible photoisomerization, and PEGylated lipid enables repetitive dosing from a single administration and enhances tissue penetration. The photoswitching allows particles to fluoresce and release drugs inside cells when illuminated with UV light. The mechanism of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
308
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 433 publications
(315 citation statements)
references
References 74 publications
4
308
0
3
Order By: Relevance
“…It has been validated that the penetration of nanoparticles in tumor space relies heavily on particle size, with the consensus that smaller particles have improved tissue penetration (26,33,44). Such progress has recently inspired interest in developing size-shrinkable anticancer drug delivery systems (15,34,45,46). Compared with previous studies, our strategy has several unique features.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been validated that the penetration of nanoparticles in tumor space relies heavily on particle size, with the consensus that smaller particles have improved tissue penetration (26,33,44). Such progress has recently inspired interest in developing size-shrinkable anticancer drug delivery systems (15,34,45,46). Compared with previous studies, our strategy has several unique features.…”
Section: Discussionmentioning
confidence: 98%
“…This is particularly important for treating poorly permeable solid tumors, because only the sub-30-nm micelles could penetrate the poorly permeable pancreatic tumors to achieve an antitumor effect (27). For previous systems, their final sizes after shrinkage were still as large as 40-70 nm (34,45,46), which is likely to offset the usefulness of size shrinkage for treating poorly permeable tumors. In our system, the released small PAMAM dendrimer prodrugs have a size of around 5 nm, which is highly potent in penetrating the intractable tumors to reach cancer cells that are far away from the blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…The sizes of Doxil and Abraxane mentioned above are approximately 100 and 130 nm, respectively, and it was found that these nanoparticles were predominantly located near the blood vessels (1). Hence, size of the nanoparticles plays a critical role in their penetration and retention within the tumor tissue (6,10,16,17). The 50 nm nanoparticles, including gold, silica, and polystyrene nanoparticles, were those that were taken up the most by monolayer cells (18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] The high surface area derives from the small geometric size of the particles leading to a high area to volume ratio which for solid spherical particles scales as the inverse of the particle radius. However, in addition, many nanoparticles are themselves composed of many smaller particles aggregated together.…”
Section: Introductionmentioning
confidence: 99%